Hemodynamic and Mechanical Properties of the Proximal Aorta in Young and Middle-Aged Adults With Isolated Systolic Hypertension: The Dallas Heart Study. Issue 1 (July 2017) - Yano, Yuichiro; Neeland, Ian J.; Ayers, Colby; Peshock, Ronald; Berry, Jarett D.; Lloyd-Jones, Donald M.; Greenland, Philip; Mitchell, Gary F.; Vongpatanasin, Wanpen
Abstract : The aim of this study was to assess characteristic impedance (Zc ) of the proximal aorta in young and middle-aged individuals with isolated systolic hypertension (ISH). Zc is an index of aortic stiffness relative to aortic size. In the Dallas Heart Study, 2001 untreated participants 18 to 64 years of age (mean age: 42.3 years; 44% black race) were divided into the following groups based on office blood pressure (BP) measurements: (1) optimal BP (systolic BP [SBP] <120 mm Hg and diastolic BP [DBP] <80 mm Hg; n=837); (2) prehypertension (SBP 120–139 mm Hg and DBP 80–89 mm Hg; n=821); (3) ISH (SBP ≥140 mm Hg and DBP <90 mm Hg; n=121); (4) isolated diastolic hypertension (SBP <140 mm Hg and DBP ≥90 mm Hg; n=44); and (5) systolic–diastolic hypertension (SBP ≥140 mm Hg and DBP ≥90 mm Hg; n=178). Zc, aortic arch pulse wave velocity, and minimum ascending aortic size were quantified using cardiovascular magnetic resonance. In multivariable-adjusted linear models, Zc was highest in the ISH group compared with the optimal BP, isolated diastolic hypertension, or systolic–diastolic hypertension groups (103.2±4.0 versus 68.3±2.1, 75.4±6.0, and 88.9±4.8 dyne*seconds/cm 5, respectively; all P <0.05). The Zc –ISH association did not differ by race. Aortic pulse wave velocity was highest in the ISH group compared with the optimal BP, isolated diastolic hypertension, or systolic–diastolic hypertension groups (6.3±0.3 versus 4.3±0.1, 4.4±0.4 and 5.5±0.3 m/s, respectively; all P <0.05), whereas aortic size was similar across groups (all P >0.2). Results were similar in a subgroup of 1551 participants 18 to 49 years of age. In a multiracial population-based sample, we found evidence of a mismatch between proximal aortic stiffness and diameter in young and middle-aged adults with ISH. Abstract : Supplemental Digital Content is available in the text.